THEMATIC PORTFOLIO IN THE SYSTEM OF PREPARING A FUTURE PRIMARY TEACHER - N.N. Yurchenko (Academy of Cognitive and Natural Sciences, 2010)
The author of the article stops on the problem of quality of professional preparation of teachers , shares with the experience of using of modern technologies at the process of teach ing of Russian Language Teaching Methodology .